Rancang Bangun Sistem Informasi Persediaan Bahan Bangunan Berbasis Website di Tb. Gilang Putra - Anjas Tryana; Santi Damayanti; Heri Purwanto (Ma'soem University, 2022)
Inventory is a very important source of information in the company where inventory is a means of supporting buying and selling for Tb. Gilang Putra. Data processed by TB. Gilang Putra's stock of goods consists of several types of building materials. Meanwhile, data processing activities are in the form of procurement of goods, recording transactions, making reports. The purpose of the study is to build a website-based building material inventory information system on Tb. Gilang Putra, which is expected to produce a more effective building material inventory system. The methods in data collection used are observation, interviews, literature studies and document studies. Using the RUP and OOAD methods where the developer tool is UML. The result of this design is in the form of a website-based building material inventory information system that can manage sales and purchases at Tb. Gilang Putra digitally. It can be concluded that this information system can be useful and is expected to run well to help the performance of employees at Tb. Gilang Putra.